Lower limb massage in humans increases local perfusion and impacts systemic hemodynamics - Monteiro Rodrigues, Luis; Rocha, Clemente; Ferreira, Hugo T; Silva, Henrique N (Journal of applied physiology (1985), 2020)
Massage is commonly used as a complementary therapy for many different conditions. Demonstration of its physiological impact and understanding of its therapeutic mechanisms is still insufficient and often inconclusive. This study aims to characterize the physiological effects of effleurage, one of the most popular techniques, on human in vivo microcirculation and its impact on cardiovascular function. Two differently oriented variations of the technique, referred to influence physiological outcomes, were applied to 32 young (mean 19.8 ± 1.6 yr old) healthy volunteers of both sexes in a single, randomly chosen limb after informed written consent. Each protocol included a 10-min baseline ( ), a 5-min massage ( ), and a 10-min recovery ( ) register. A 30-min washout period separated both protocols. Perfusion was assessed by laser Doppler flowmetry (LDF) and reflection photoplethysmography (PPG), with their sensors applied distally in both feet. Blood pressure and pulse were also obtained. LDF signals were further analyzed in their components by the (Morlet) wavelet transform to probe the mechanisms involved. Results showed that effleurage consistently evoked a significant ( < 0.001) perfusion increase in the massaged limb, also visible in the contralateral limb (not significant) independently from the orientation (variant) used. No matter the perfusion differences known between sexes, the adaptive response was equivalent in both sexes. The component analysis of the LDF curves also suggests that these procedures, although brief and superficial, do modify multiple components of cardiovascular integration, with cardiac, respiratory, and myogenic components appearing to play a major role in reestablishing distal microcirculatory homeostasis. The impact of effleurage, a well-known massage procedure used in human rehabilitation, in the lower limb hemodynamics, is demonstrated. When applied in a sole limb, massage increases skin microcirculatory flowmotion not only locally but also beyond, affecting systemic hemodynamics. This observation is an interesting example of the efficacy of cardiovascular integration mechanisms involving distal microcirculatory homeostasis. The proposed methodology allows a mechanistic view over skin flowmotion regulation, being applicable to further explore massage and its impact on microcirculatory physiology.